Guidance on the preparation and presentation of the notification and application for authorisation of traditional foods from third countries in the context of Regulation (EU) 2015/2283. (10th November 2016) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following the adoption of Regulation (EU) 2015/2283 of the European Parliament and of the Council on Novel Foods, the European Commission requested EFSA to develop a scientific and technical guidance for the preparation and presentation of notifications for traditional foods from third countries. This guidance presents a common format for the organisation of the information to be presented in order to assist the applicant in the preparation of a well‐structured dossier. The safety of a traditional food should be substantiated by reliable data on its composition, its experience of continued use and its proposed conditions of use. Besides, its normal consumption should not be nutritionally disadvantageous. To that end, information is requested on the description, production process, composition, stability data, specifications, data from experience of continued use in a third country and on the proposed conditions of use of the traditional food for the EU market. The structure of the notification dossier should follow the sections presented in this guidance. This guidance is also intended to support applicants in providing the type and quality of information EU Member States and EFSA need for the assessments of traditional foods from third countries. The application should be comprehensive and complete. The applicant should integrate the information on the composition and the experience of continued use and provide a concise overall consideration on how this substantiates the history of safe use of the traditional food and how this relates to the proposed conditions of use for the EU. Where potential health hazards have been identified on the basis of the composition and/or data from the experience of continued use, they should be discussed. On the basis of the information provided, EFSA will assess the safety related to the consumption of the traditional food under the proposed conditions of use. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2016.EN-1108/full